2005
DOI: 10.1103/physrevc.72.024312
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine anomaly in Be isotopes in the cluster model and the neutron spatial distribution

Abstract: The study of the hyperfine (hfs) anomaly in neutron rich nuclei can give a very specific and unique way to study the neutron distribution and the clustering structure. We study the sensitivity of the hfs anomaly to the clustering effects in the 9 Be isotope using two different nuclear wave functions obtained in the three-cluster (α + α + n) model. The results are compared to those obtained for 9,11 Be in a two-body core + neutron model to examine whether the hfs anomaly is sensitive to a halo structure in 11 B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(53 citation statements)
references
References 40 publications
(139 reference statements)
2
51
0
Order By: Relevance
“…The shares of the events Θ n and Θ w constitute 0.56±0.04 and 0.44±0.04, respectively. These values demonstrate the compliance with the weights of the 8 Be 0 + and 2 + states adopted in [48,49] and point to the presence of these states as components of the 9 Be ground state.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The shares of the events Θ n and Θ w constitute 0.56±0.04 and 0.44±0.04, respectively. These values demonstrate the compliance with the weights of the 8 Be 0 + and 2 + states adopted in [48,49] and point to the presence of these states as components of the 9 Be ground state.…”
supporting
confidence: 65%
“…In the two-body model used for the calculation of the magnetic moment [48,49] of the 9 Be nucleus, the latter is represented as a bound state of the neutron and 8 Be core in the 0 + For events Θ vw an important factor is the accuracy of the determination of energy and of identification of He isotopes. Thus, the formation of Θ n pairs is matched to decays of the 8 Be 0 + ground state and Θ w pairs − of the first excited 2 + state.…”
mentioning
confidence: 99%
“…In our investigation of the 2α + n structure of the 9 Be nucleus [7], it was found that the 9 Be → 2α fragmentation process proceeds with close probabilities through the 0 + and 2 + states of the 8 Be nucleus. These probabilities show correspondence with the weights assigned to the 0 + and 2 + states of the 8 Be nucleus in calculating the magnetic moment of the 9 Be nucleus on the basis of cluster wave functions [14,15]. Data on the relativistic fragmentation of 9 Be nuclei [7] can be considered as the proof that, with a high probability,…”
Section: Search For Events Involving 3 3 Hementioning
confidence: 71%
“…The goal of these hyperfine structure measurements is to determine the magnetization radius through the Bohr-Weisskopf effect [17][18][19][20]. For this purpose, we need to know the nuclear magnetic moments (or g-factors) with high accuracies which should independently be determined from the hyperfine constants.…”
Section: Optical Spectroscopy Of Beryllium Isotopesmentioning
confidence: 99%